Wodyetia bifurcata, Foxtail Palm - Mary McKenzie; Michael G. Andreu; Melissa H. Friedman; Heather V. Quintana (EDIS)
FOR 242, a 2-page fact sheet by Mary McKenzie, Michael G. Andreu, Melissa H. Friedman, and Heather V. Quintana, describes this palm endemic to the scrublands of the rocky northeastern peninsula of Australia — scientific and common names, description, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.